Factors behind support for harsher punishments for common and uncommon offenders. Issue 2 (10th April 2017) - Palasinski, Marek; Shortland, Neil
Abstract : Purpose: The purpose of this paper is to explore individual factors predicting support for harsher punishments for relatively common and uncommon serious offenders. Design/methodology/approach: In Study 1, 120 UK participants (60 males and 60 females; mean age =37.31 SD=16.74) completed a survey exploring the extent to which they supported harsher punishments (SHP) for first time and repeat fraud, sexual and violent offenders. In Study 2, 131 participants (70 Britons and 61 Singaporeans; 69 females and 62 males; mean age=31.57; SD=10.87) completed a similar survey exploring their support for life sentence without the possibility of parole (SLSWP) for rather uncommon repeat offenders (i.e. drug traffickers, human traffickers, serious sexual offenders). Findings: Study 1 found that right-wing authoritarianism (RWA) was an SHP predictor for first time and repeat fraud, violent and sex offenders. Study 2 found that national identity (i.e. how British or Singaporean participants felt) played a similar role to Study 1's RWA in being a positive SLSWP predictor for repeat human traffickers and drug traffickers of both sexes, as well as male sex offenders. In contrast to the hypothesis, however, participants' locations did not appear to play a statistically significant role. Research limitations/implications: This survey-based research reveals a nuanced and quite consistent picture that could benefit from the inclusion of socio-economic factors and other cross-cultural comparisons. Practical implications: The key message from this study is to inform the public on the role that right-wing authoritarianism and national identity play in their SHP and SLSWP. Social implications: It is vital to increase the legislators' and the public awareness of the role that national identity and RWA seem to play. Originality/value: The paper offers insight into factors behind people's punitive attitudes towards specific crimes regardless of geo-cultural location.